Deciphering the Mechanism of Melatonin-Induced Enhancement of Photosystem II Function in Moderate Drought-Stressed Oregano Plants - Moustaka, Julietta; Sperdouli, Ilektra; İŞGÖREN, SUMRUNAZ; Şaş, Begüm; Moustakas, Michael (MDPI, 2024)
Melatonin (MT) is considered as an antistress molecule that plays a constructive role in the acclimation of plants to both biotic and abiotic stress conditions. In the present study, we assessed the impact of 10 and 100 μM MT foliar spray, on chlorophyll content, and photosystem II (PSII) function, under moderate drought stress, on oregano (Origanum vulgare L.) plants. Our aim was to elucidate the molecular mechanism of MT action on the photosynthetic electron transport process. Foliar spray with 100 μM MT was more effective in mitigating the negative impact of moderate drought stress on PSII function, compared to 10 μM MT. MT foliar spray significantly improved the reduced efficiency of the oxygen-evolving complex (OEC), and PSII photoinhibition (Fv/Fm), which were caused by drought stress. Under moderate drought stress, foliar spray with 100 μM MT, compared with the water sprayed (WA) leaves, increased the non-photochemical quenching (NPQ) by 31%, at the growth irradiance (GI, 205 μmol photons m−2 s−1), and by 13% at a high irradiance (HI, 1000 μmol photons m−2 s−1). However, the lower NPQ increase at HI was demonstrated to be more effective in decreasing the singlet-excited oxygen (1O2) production at HI (−38%), in drought-stressed oregano plants sprayed with 100 μM MT, than the corresponding decrease in 1O2 production at the GI (−20%), both compared with the respective WA-sprayed leaves under moderate drought. The reduced 1O2 production resulted in a significant increase in the quantum yield of PSII photochemistry (ΦPSII), and the electron transport rate (ETR), in moderate drought-stressed plants sprayed with 100 μM MT, compared with WA-sprayed plants, but only at the HI (+27%). Our results suggest that the enhancement of PSII functionality, with 100 μM MT under moderate drought stress, was initiated by the NPQ mechanism, which decreased the 1O2 production and increased the fraction of open PSII reaction centers (qp), resulting in an increased ETR. © 2024 by the authors.
Keywords: Chlorophyll Content; Electron Transport; Excess Excitation Energy; Non-photochemical Quenching; Photoinhibition; Quantum Yield of PSII Photochemistry; Redox State; Singlet-excited Oxygen